2020
DOI: 10.1021/acsami.0c02021
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Engineering of Fe/Fe3C-Decorated Metal–Nitrogen–Carbon Mesoporous Nanospheres via a Self-Template Method for Enhancing Oxygen Reduction Activity

Abstract: We report a self-template and facile pyrolysis method to synthesize Fe/Fe3C-decorated metal–nitrogen–carbon mesoporous nanospheres, of which preserved plum-like and hollow structures can be simply engineered via controlling the thickness of the outermost polydopamine layer in the precursors. The preserved plum-like structure is demonstrated to show a large electrochemically active surface area and facilitate fast charge transfer, in comparison with the hollow one. The catalytic activities of metal–nitrogen–car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In another work, Fe/Fe 3 C-decorated M-N-C mesoporous nanospheres have been designed, whose catalytic activities of M-N-C and nitrogen-doped carbon active sites in the outer carbon layer toward ORR are further improved by the activation of the encased iron species. Specifically, the encased iron species can promote the ORR catalytic performance of the M-N-C active sites in the surrounding carbon shells by strengthening the oxygen molecule’s adsorption . Furthermore, it is popular accepted that the metal-based nanoparticles suffer from low stability due to the corrosion phenomenon in the acid medium, leading to hard identification of active sites and short lifetime of the catalysts in acid.…”
Section: Synergistic Modulation Of Active Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Fe/Fe 3 C-decorated M-N-C mesoporous nanospheres have been designed, whose catalytic activities of M-N-C and nitrogen-doped carbon active sites in the outer carbon layer toward ORR are further improved by the activation of the encased iron species. Specifically, the encased iron species can promote the ORR catalytic performance of the M-N-C active sites in the surrounding carbon shells by strengthening the oxygen molecule’s adsorption . Furthermore, it is popular accepted that the metal-based nanoparticles suffer from low stability due to the corrosion phenomenon in the acid medium, leading to hard identification of active sites and short lifetime of the catalysts in acid.…”
Section: Synergistic Modulation Of Active Sitesmentioning
confidence: 99%
“…Specifically, the encased iron species can promote the ORR catalytic performance of the M-N-C active sites in the surrounding carbon shells by strengthening the oxygen molecule's adsorption. 66 Furthermore, it is popular accepted that the metal-based nanoparticles suffer from low stability due to the corrosion phenomenon in the acid medium, leading to hard identification of active sites and short lifetime of the catalysts in acid. Carbon layer coating on the metallic nanoparticles has been proposed to improve the acid stability of the M-N-C active sites.…”
Section: Synergistic Modulation Of Active Sitesmentioning
confidence: 99%
“…10,11 However, some other research discovered that metal particles, such as Fe particles, can react with carbon to produce Fe 3 C structures wrapped in carbon layers under heating; these particles have been considered as the ORR active sites and synergetically improve the activity of FeN x sites. [12][13][14] Some researchers have employed chemical corrosion to remove and destroy particles containing Fe 3 C. A decrease in the half-wave potential was measured in these studies, indicating that the Fe 3 C particles generated through sintering promote the ORR activity of catalysts. 15,16 Moreover, sintered transition metal particles can catalyse the synthesis of carbon nanotubes (CNTs), a conductive material that can enhance the performance of electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yu et al fabricated a three-dimensional hierarchical porous carbon nanomelt network using a simple pyrolysis method with porous materials as templates . She et al reported the synthesis of metal–nitrogen–carbon mesoporous nanospheres by a self-template and facile pyrolysis method …”
Section: Introductionmentioning
confidence: 99%
“…38 She et al reported the synthesis of metal− nitrogen−carbon mesoporous nanospheres by a self-template and facile pyrolysis method. 39 In this study, DS−Fe−N−HC's were synthesized through a novel pyrolysis method with porous Fe 3 O 4 microspheres as the template and pyrrole monomers as C and N precursors. This new strategy can eliminate the adverse effects of the traditional methods during the removal of the hard template.…”
Section: ■ Introductionmentioning
confidence: 99%